2019
DOI: 10.21203/rs.2.17380/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gender differences in subliminal affective face priming: A high-density ERP study

Abstract: Background Subliminal affective priming effects (SAPEs) refer to the phenomenon by which the presentation of an affective prime stimulus influences the subsequent affective evaluation of a target stimulus. Previous studies have shown that behavioural performance is affected more by unconsciously processed stimuli than by consciously processed stimuli. However, the impact of SAPEs on the face-specific N170 component is unclear. In the current study, we investigated how subliminal processing of fearful faces aff… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 70 publications
(99 reference statements)
3
4
0
Order By: Relevance
“…Consistent with our previous study [7], the behavioral data revealed no priming or group effects. Emotional recognition in ASD is currently controversial, with mixed evidence regarding atypical and typical responses in ASD [24].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with our previous study [7], the behavioral data revealed no priming or group effects. Emotional recognition in ASD is currently controversial, with mixed evidence regarding atypical and typical responses in ASD [24].…”
Section: Discussionsupporting
confidence: 92%
“…We used neutral and fearful expressions displayed by four Japanese actors (two men and two women) as prime-face stimuli, following our previous study [7]. Target-face stimuli including neutral and fearful expressions displayed by another four Japanese actors were used as prime-face stimuli.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations